“Las TIC en el área de lengua y literatura” - Falcón Prieto, Katerin Dayanara (2023)
Every day the world benefits from technology, which offers a series of advantages, especially in the educational field, where it has revolutionized the way of teaching and learning, which is why, within the Teaching-Learning Process, the implementation of ICTs significantly favors the realization and acquisition of knowledge. In this sense, the research project called "ICT in the language and literature area" seeks that teachers apply them within the different stages of teaching in order to achieve academic progress and the deepening of knowledge. The objective of this research is to consolidate the teaching and learning process through the application of audiovisual resources in the Language and Literature area in the fourth grade of the Basic Education School "Numa Pompilio Llona" in Latacunga, Cotopaxi Province. In this way, a qualitative methodological design was applied, due to the fact that in the process it is necessary to validate all the descriptions detailed by the researchers in the respective instruments in order to proceed to make the respective reflections. The instrument used was the observation guide in which results of significant learning were obtained. By applying ICTs in the teaching and learning process in the area of language and literature, an improvement in the understanding of the topics is observed, as well as a favorable development of the learning skills oriented by the teacher. The application of audiovisual resources in the development of language and literature classes favors the teacher's work in the classroom, since it offers information and content in a systematized and innovative way, which contributes to the student's consolidation and appropriation of concepts.